2017
DOI: 10.1038/srep41962
|View full text |Cite
|
Sign up to set email alerts
|

PARP-1/PARP-2 double deficiency in mouse T cells results in faulty immune responses and T lymphomas

Abstract: The maintenance of T-cell homeostasis must be tightly regulated. Here, we have identified a coordinated role of Poly(ADP-ribose) polymerase-1 (PARP-1) and PARP-2 in maintaining T-lymphocyte number and function. Mice bearing a T-cell specific deficiency of PARP-2 in a PARP-1-deficient background showed defective thymocyte maturation and diminished numbers of peripheral CD4+ and CD8+ T-cells. Meanwhile, peripheral T-cell number was not affected in single PARP-1 or PARP-2-deficient mice. T-cell lymphopenia was as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
61
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 61 publications
(85 reference statements)
2
61
0
Order By: Relevance
“…In fact, p53 deficiency restores thymocyte populations in PARP-2-deficient mice [15]. In contrast, PARP-1 regulates tTreg development [16], while PARP-2 does not seem to play any role in tTreg development [17] (Figure 1).…”
Section: Impact Of Parp-1 and Parp-2 On T Cell Development And Functionmentioning
confidence: 96%
See 2 more Smart Citations
“…In fact, p53 deficiency restores thymocyte populations in PARP-2-deficient mice [15]. In contrast, PARP-1 regulates tTreg development [16], while PARP-2 does not seem to play any role in tTreg development [17] (Figure 1).…”
Section: Impact Of Parp-1 and Parp-2 On T Cell Development And Functionmentioning
confidence: 96%
“…Although PARP-1 deficiency or PARP-2 deficiency alone does not affect the number of T cells in peripheral lymphoid tissues [14,17], double deficiency in the T cell compartment results in a significant decrease in both CD4 + and CD8 + peripheral T cells [17]. The T cell lymphopenia present in mice with double PARP-1 and PARP-2 deficiency indicates that these proteins act in a coordinated manner to prevent the accumulation of unrepaired DNA breaks upon homeostatic proliferation or in response to antigen challenge, but not under basal conditions, avoiding T cell death [17]. PARP-1 and PARP-2 likely act through the principle of synthetic lethality [22], whereby they regulate two Although both PARP-1 and PARP-2 proteins are expressed in thymocytes [14], only PARP-2 plays a significant role in thymocyte development.…”
Section: Impact Of Parp-1 and Parp-2 On T Cell Development And Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional studies used PARP1-deficiet mice further demonstrated mechanisms for PARP1-regulated suppression of Tregs via transforming growth factor β (TGF β) receptors . Recent reports demonstrate the interactive role of PARP1 and PARP2 in maintaining the number and function of T cells and promoting the development and function of B cells (Navarro et al 2017;Galindo-Campos et al 2019). Defective thymocyte maturation is observed in PARP1/PARP2-deficient mice, and accordingly T-cell numbers in peripheral blood are reduced (Galindo-Campos et al 2019).…”
Section: Parp1 Participates In the Biology Of Other Immune Cellsmentioning
confidence: 99%
“…Defective thymocyte maturation is observed in PARP1/PARP2-deficient mice, and accordingly T-cell numbers in peripheral blood are reduced (Galindo-Campos et al 2019). In PARP1/PARP2-deficient mice, the development of bone marrow B cells is impaired, leading to the reduction of transitional and follicular B cells (Navarro et al 2017). PARP1 also plays a role in the maturation and function of dendritic cells by regulating the production of IL-10 and IL-12 (Aldinucci et al 2007).…”
Section: Parp1 Participates In the Biology Of Other Immune Cellsmentioning
confidence: 99%